Thermoelectrics for Power Generation - A Look at Trends in the Technology 2016
DOI: 10.5772/65864
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Thermoelectric Materials Based on Solid Solutions of Mg2X Compounds (X = Si, Ge, Sn)

Abstract: The silicides have obvious atractive characteristics that make them promising materials as thermoelectric energy converters. The constituting elements are abundant and have low price, many of compounds have good high temperature stability. Therefore, considerable eforts have been made, especially in the past 10 years, in order to develop eicient silicide-based thermoelectric materials. These eforts have culminated in creation of Mg 2 (Si-Sn) n-type thermoelectric alloys with proven maximum thermoelec-tric igur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…These properties make them very attractive to industries such as aerospace and automotive . The binary Mg 2 Si has been thoroughly studied, , and contact development has shown promising results. Ni worked well as a contacting electrode with Mg 2 Si showing good adhesion, low specific contact resistance (<10 μΩ·cm 2 ), and temperature stability. , …”
Section: Introductionmentioning
confidence: 99%
“…These properties make them very attractive to industries such as aerospace and automotive . The binary Mg 2 Si has been thoroughly studied, , and contact development has shown promising results. Ni worked well as a contacting electrode with Mg 2 Si showing good adhesion, low specific contact resistance (<10 μΩ·cm 2 ), and temperature stability. , …”
Section: Introductionmentioning
confidence: 99%
“…The complete solubility of Mg 2 Si 1−x Ge x has been successfully demonstrated 15,24-27 . In the remaining Mg 2 X 1−x Sn x systems, X = Si, Ge, the experiments on solid solutions have shown that solubility depends rather upon the preparation method and experimental conditions 23,28,29 . No complete and stable solubility has been demonstrated 1 .…”
mentioning
confidence: 99%